Integrative Single-Cell RNA-Seq and ATAC-Seq Analysis of Peripheral Mononuclear Cells in Patients With Ankylosing Spondylitis - Xu, Huixuan; Yu, Haiyan; Liu, Lixiong; Wu, Hongwei; Zhang, Cantong; Cai, Wanxia; Hong, Xiaoping; Liu, Dongzhou; Tang, Donge; Dai, Yong (Frontiers in Immunology, 2021)
Objective: Genetic studies on ankylosing spondylitis (AS) have identified more than 100 pathogenic genes. How to build a bridge between these genes and biologically targeted therapy is the current research hotspot. Methods: Our research integrates single-cell assaying transposase accessible chromatin sequencing (scATAC-seq) and single-cell RNA sequencing (scRNA-seq) to explore the key genes and related mechanisms associated with AS patheogensis. Results: As a result, we identified 18 cell types in peripheral mononuclear cells from AS patients and normal controls and summarized the cell-type specific abnormal genes by scRNA-seq. Interestingly, we found that the pathogenic gene NFKB involved in AS progression came from CD8+ T cells. Moreover, we observed an abnormal TNF signaling pathway mediated by abnormal expression of TNF, NFKB, FOS, JUN, and JUNB, and our scATAC-seq results confirmed the abnormal accessible binding sites of transcriptional factors FOS, JUN, and JUNB. The final magnetic bead sorting and RT-QPCR confirmed that NFKB, FOS, JUN, and JUNB in CD8+Tcell did differ in AS group. Conclusions: Our results revealed the possible mechanism that NFKB abnormally regulates FOS, JUN, and JUNB and drives AS progression, providing a novel perspective from a single cell point of view in AS.